2020
DOI: 10.12659/msm.920211
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Hydrogen-Rich Water Against Cartilage Damage in a Rat Model of Osteoarthritis by Inhibiting Oxidative Stress, Matrix Catabolism, and Apoptosis

Abstract: Background: The aim of this study was to investigate the mechanisms underlying the potential effects of hydrogen-rich water (HW) on articular cartilage in a rat osteoarthritis (OA) model. Material/Methods: A rat model of OA was established using the modified Hulth method, and rats were forced to exercise for 30 min every day 1 week after surgery for 7 weeks. Mankin's method was used to score the severity of OA. The animals were assigned into the OA group, OA+HW group, and sham operation group. After 8 weeks, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The antidepressant and anxiolytic properties of this gas have also been described [ 21 , 22 ]. Moreover, several studies have demonstrated the anti-inflammatory properties of H 2 ; in animals with osteoarthritis [ 23 ] and its antinociceptive effects in preclinical models of neuropathic pain caused by nerve injury [ 24 , 25 , 26 ]. A recent study further reveals that treatment with hydrogen-rich water (HRW) inhibits the affective disorders accompanying neuropathic pain caused by nerve damage [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antidepressant and anxiolytic properties of this gas have also been described [ 21 , 22 ]. Moreover, several studies have demonstrated the anti-inflammatory properties of H 2 ; in animals with osteoarthritis [ 23 ] and its antinociceptive effects in preclinical models of neuropathic pain caused by nerve injury [ 24 , 25 , 26 ]. A recent study further reveals that treatment with hydrogen-rich water (HRW) inhibits the affective disorders accompanying neuropathic pain caused by nerve damage [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of Fer-1 or ScpI2 to intervene in human primary chondrocytes from the early-stage OA could significantly improve cell viability. As such, 5-week modified-Hulth models were employed to simulate early-stage OA (identified by Safranin O/fast green staining) in rats [ 40 ]. Besides discovering that the SCP2 inhibitor ScpI2 reduced ferroptosis markers such as iron, ACSL4 and MDA in rat OA cartilage, ScpI2 also relieved the symptoms of OA which was consistent with the results of cartilage anabolism genes expression in vitro study, suggesting that articular injection of ScpI2 suppressed ferroptosis in chondrocytes thereby alleviating the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Meanwhile, studies have also found that oral H 2 -rich water or local injection of H 2 sustained-release system into the knee joint can delay the development of knee osteoarthritis. 66 68 …”
Section: Olecular M Echanism Of H ...mentioning
confidence: 99%